HUBUNGAN KELEBIHAN BERAT BADAN DENGAN PERUBAHAN KONSEP DIRI PADA MAHASISWA AKPER PANTI KOSALA SURAKARTA - Tunjung Sri Yulianti; Dinar Ariasti; Dewi Novita Sari (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Being overweight is a condition where a person has a weightheavier and than ideal weight. While the self concept of individuals is all ideas,thoughts and beliefs which is known and undestanded by theirself.The Purpose of this study was to determine the relationship between overweight and changes in self concept of the students of Panti Kosala Surakartanursing academy by 2013.Subject used in this study were the students of Panti Kosala Surakarta nursingacademy. The sampling was total sampling and the number of sampling were30 students.Methods This study was held at Panti Kosala Surakarta nursing academy, usedthe correlation method with cross sectional approach. Data were collected usinga queshionare test with significance level Î± = 0,05.The Conclusion The result showed x2 count < x2 table (7,3668 < 9,448). It canbe concluded that there was no relation between overweight and changing inself concept of individuals.Keywords : Overweight, Self Concept